Compatibility of a Gaseous Dielectric with Al, Ag, and Cu and Gas-Phase Synthesis of a New N-Acylamidine Copper Complex - Kessler, Florian; Sarfert-Gast, Wiebke; Kuhlmann, Laura; Ise, Martin; Heinemann, Frank Wilhelm (European Journal of Inorganic Chemistry, 2020)
Herein we describe the compatibility of 2-(trifluoromethyl)-2,3,3,3-tetrafluoropropane nitrile, an insulating gas for gas-insulated equipment, with aluminum, silver and copper. In an autoclave metal samples, oxygen, the gaseous 2-(trifluoromethyl)-2,3,3,3-tetrafluoropropane nitrile and a small amount of water were mixed at elevated pressure and heated up to 225 °C for several weeks. When Cu was present a multi-step gas phase reaction occurred, and single crystals of a copper complex were isolated. The square planar copper(II) complex contains two perfluorinated N-acylamidine ligands. The structure of the complex was obtained by single-crystal X-ray diffraction.
CRIS-Team Scopus Importer:2020-04-28
Keywords: Amides; Copper; Fluorine; Gas-phase reactions; N; O ligands